Implementación tecnológica en el manejo de drones para la fertilización foliar en el cultivo de cacao (Theobroma cacao) - Molina Loor, Wellington Enrique (2023)
The research topic arises due to the great shortcomings and problems faced by producers due to mismanagement or traditional use of techniques which can be replaced by systems, programs or technological applications which allow constant appropriate control for crop management within the different stages of it. The objective of this research is to analyze the potential of the use of drones in the foliar fertilization of cocoa crops, studying the characteristics, benefits and challenges associated with this technology, it seeks to determine if the use of drones can improve the efficiency of foliar fertilization, optimizing the supply of nutrients and, ultimately, increasing the yield and quality of cocoa crops compared to traditional fertilizer application methods. In conclusion, it seeks to provide a comprehensive view on the use of drones as a means of optimal performance in foliar fertilization for cocoa crops. It is expected that the results obtained will contribute to the effective implementation of this technology in cocoa agriculture, offering a promising alternative to improve the productivity and sustainability of crops, as well as the economic well-being of farmers